Viscum album mother tinctures: Harvest conditions and host trees influence the plant metabolome and the glycolytic pathway of breast cancer cells - Melo, Michelle Nonato de Oliveira; Ochioni, Alan Clavelland; Zancan, Patricia; Oliveira, Adriana Passos; Grazi, Mirio; Garrett, Rafael; Holandino, Carla; Baumgartner, Stephan (Frontiers in Pharmacology, 2022)
Viscum album is a semi-parasitic plant used for over one hundred years in complementary cancer therapy. The main commercial drugs used in cancer patients’ treatment are derived from the aqueous V. album extracts, whose cytotoxic potential is mostly attributed to the aqueous soluble antitumoral metabolites. On the counterpart, ethanol solvents must be used to obtain V. album mother tinctures. This methodology permits better solubilization of phenolic compounds, among others, which present antitumoral bioactivity. Recently, the metabolomics approach revealed the influence of the host tree on the V. album subspecies differentiation. To increase the scientific information about the chemical differences related to the host trees and to clarify the seasonal influences, in this study, the metabolome of fifty V. album mother tinctures from three subspecies (abietis, album, austriacum) and five host trees (Malus domestica, Quercus sp., Ulmus carpinifolia, Pinus sylvestris, Abies alba) was evaluated using summer and winter plant harvests. The in vitro cytotoxic activities were investigated in breast cancer cells (MDA-MB-231) and immortalized normal human keratinocytes (HaCat). The summer V. album mother tinctures presented higher cytotoxic activity than winter ones. Among the summer samples, those prepared with V. album subsp. album were more cytotoxic than V. album subsp. abietis and subsp. austriacum. The V. album harvested from Quercus petraea and Abies alba inhibited the key-glycolytic enzymes: hexokinase (HK), phosphofructokinase (PFK), pyruvate kinase (PK). This activity was related to a reduction in glucose uptake and lactate production, which were host-tree-time-dose-dependent. The untargeted metabolomic approach was able to discriminate the mother tinctures according to respective botanical classes and harvest season. A total of 188 metabolites were annotated under positive and negative modes. Fourteen compounds were responsible for the samples differentiation, and, to the best of our knowledge, eight were described in the Viscum album species for the first time. Our study shows the interruption of the Warburg effect as a novel antitumoral mechanism triggered by V. album mother tinctures, which is related to their metabolite profile. These results bring scientific evidence that encourages the use of V. album mother tinctures as a natural product for cancer therapy.